Allogenic microglia replacement: A novel therapeutic strategy for neurological disorders - Yanxia Rao; Bo Peng (Fundamental Research, 2024)
Microglia are resident immune cells in the central nervous system (CNS) that play vital roles in CNS development, homeostasis and disease pathogenesis. Genetic defects in microglia lead to microglial dysfunction, which in turn leads to neurological disorders. The correction of the specific genetic defects in microglia in these disorders can lead to therapeutic effects. Traditional genetic defect correction approaches are dependent on viral vector-based genetic defect corrections. However, the viruses used in these approaches, including adeno-associated viruses, lentiviruses and retroviruses, do not primarily target microglia; therefore, viral vector-based genetic defect corrections are ineffective in microglia. Microglia replacement is a novel approach to correct microglial genetic defects via replacing microglia of genetic defects with allogenic healthy microglia. In this paper, we systematically review the history, rationale and therapeutic perspectives of microglia replacement, which would be a novel strategy for treating CNS disorders.